Osmotically dehydrated microwave vacuum drying of carrots - V. Changrue (2018)
Osmotic dehydration prior to drying was able to remove free water, which accounts for around 50% of the product's moisture. The combination of osmotic and microwave vacuum drying was investigated. The advantage of microwave vacuum drying is that it provides faster drying times with a low-temperature process. Since solid gain from osmotic agents might cause a decrease in diffusivity of the osmotically dehydrated product and lower qualities of dried product, it is important to know the effects of osmotic treatment prior to microwave vacuum drying. Two levels of microwave input power (1 and 1.5W/g) and three power modes (continuous, 45 s on/15s off and 30 s on/30 s off) were studied at an absolute pressure of 8 kPa for the microwave vacuum drying of carrots. Drying kinetics, energy consumption, and quality in terms of water activity, shrinkage, rehydration capacity, color characteristics, and sensory evaluation were studied. Empirical models were established to fit the observed data. In general, osmotic dehydration was able to decrease drying time and energy consumption. Less shrinkage and improved appearance were the advantages in terms of quality. Page's model showed the best fit among the tested models.